Current Technological Improvements in Enzymes toward Their Biotechnological Applications - Baweja, Mehak; Nain, Lata; Kawarabayasi, Yutaka; Shukla, Pratyoosh (Frontiers in Microbiology, 2016)
Enzymes from extremophiles are creating interest among researchers due to their unique properties and the enormous power of catalysis at extreme conditions. Since community demands are getting more intensified, therefore, researchers are applying various approaches viz. metagenomics to increase the database of extremophilic species. Furthermore, the innovations are being made in the naturally occurring enzymes utilizing various tools of recombinant DNA technology and protein engineering, which allows redesigning of the enzymes for its better fitment into the process. In this review, we discuss the biochemical constraints of psychrophiles during survival at the lower temperature. We summarize the current knowledge about the sources of such enzymes and their in vitro modification through mutagenesis to explore their biotechnological potential. Finally, we recap the microbial cell surface display to enhance the efficiency of the process in cost effective way.